Diverging Patterns of Education Premium and School Attendance in France and the US: A Walrasian View - David de la Croix; Frédéric Docquier (Institute for the Study of Labor (IZA), 2003)
We evaluate the effect of technology, demographics and policy on the differential evolution of the skill premium and on the rise in education investment in France and the USA. We use a computable general equilibrium model with overlapping generations of individuals, and endogenous education decisions. Human capital is made of two substitutable components, experience and education, both of them evolve endogenously over time. We calibrate this model on the post-war period and run counterfactual experiments to assess the effect of the different exogenous variables. French expansionary education policy boosted the supply of skills and kept the skill premium low. On the contrary, increasing education costs in the US contributed to increase wage differentials by reducing the supply of skills. The skill biased technical shock is key to understand rising school attendance and appears delayed in France.
Keywords: D58; J31; 330; human capital; education; experience; skill premium; Bildungsertrag; Bildungsinvestition; Qualifikation; Bildungsökonomik; Overlapping Generations; Allgemeines Gleichgewicht; Technischer Fortschritt; Theorie; Frankreich; Vereinigte Staaten